Natural hazard threats to pollinators and pollination. (16th October 2019) - Nicholson, Charlie C.; Egan, Paul A.
Abstract: Natural hazards are naturally occurring physical events that can impact human welfare both directly and indirectly, via shocks to ecosystems and the services they provide. Animal‐mediated pollination is critical for sustaining agricultural economies and biodiversity, yet stands to lose both from present exposure to natural hazards, and future climate‐driven shifts in their distribution, frequency, and intensity. In contrast to the depth of knowledge available for anthropogenic‐related threats, our understanding of how naturally occurring extreme events impact pollinators and pollination has not yet been synthesized. We performed a systematic review and meta‐analysis to examine the potential impacts of natural hazards on pollinators and pollination in natural and cultivated systems. From a total of 117 studies (74% of which were observational), we found evidence of community and population‐level impacts to plants and pollinators from seven hazard types, including climatological (extreme heat, fire, drought), hydrological (flooding), meteorological (hurricanes), and geophysical (volcanic activity, tsunamis). Plant and pollinator response depended on the type of natural hazard and level of biological organization observed; 19% of cases reported no significant impact, whereas the majority of hazards held consistent negative impacts. However, the effects of fire were mixed, but taxa specific; meta‐analysis revealed that bee abundance and species richness tended to increase in response to fire, differing significantly from the mainly negative response of Lepidoptera. Building from this synthesis, we highlight important future directions for pollination‐focused natural hazard research, including the need to: (a) advance climate change research beyond static "mean‐level" changes by better incorporating "shock" events; (b) identify impacts at higher levels of organization, including ecological networks and co‐evolutionary history; and (c) address the notable gap in crop pollination services research—particularly in developing regions of the world. We conclude by discussing implications for safeguarding pollination services in the face of global climate change. Abstract : In contrast to the depth of knowledge available for anthropogenic‐related threats, our understanding of how naturally occurring extreme events impact pollinators and pollination has not yet been synthesized. We performed a systematic review and meta‐analysis to examine the potential impacts of natural hazards on pollinators and pollination in natural and cultivated systems. The majority of hazards held consistent negative impacts, whereas 19% of cases reported no significant impact, and fire effects were mixed but pollinator taxa specific. The distribution of these studies in space (a), time (b), and methodological approach (c) varied according to hazard type.